A continuous location and maintenance routing problem for offshore wind farms: Mathematical models and hybrid methods. (August 2022) - Irawan, Chandra Ade; Salhi, Said; Chan, Hing Kai
Abstract: In this study, we examine a challenging green logistical problem encountered with offshore wind farms: the integrated continuous location and maintenance routing problem wherein a service operation vessel and a safe transfer boat are used to maintain offshore turbines. Our aim is to dynamically and simultaneously determine the best locations for the service operation vessel in the plane (i.e. the sea) and the best delivery and pick-up routes by which the safe transfer boat can access the turbines. An optimisation model of the problem is first developed based on mixed-integer nonlinear programming to minimise the total maintenance cost. Given the limitations of this method, a novel algorithm that integrates a genetic algorithm, variable neighbourhood search, and a Weiszfeld-based algorithm is presented. To assess the performance of the proposed technique, a guided multi-start approach and a hybrid technique based on particle swarm optimisation are introduced. Moreover, our proposed method is shown to be easily adaptable to produce results that compete with those of state-of-the-art methods when it comes to solving a related continuous location routing problem. The computational results demonstrate the effectiveness and robustness of the proposed hybrid method. Highlights: A new MINLP model for the continuous location and maintenance routing problem. A Hybrid Algorithm integrating Genetic Algorithm and Variable Neighbourhood Search. An new iterative approach based on Weiszfeld to find best locations in the plane. Managerial insights obtained from extensive experimental results.